Clinical profile of scrub typhus patients in a tertiary care centre in Himachal Pradesh, India - Sharma, Ritin; Lal, Roshan; Mahajan, Sanjay; Chaudhary, Satish (International Journal of Research in Medical Sciences, 2019)
Background: Scrub typhus a zoonotic disease caused by gram negative bacteria O. tsutsugamushi, is endemic in Himachal Pradesh. This illness occurs mainly in monsoon and post monsoon season. study design of this study was conducted in a tertiary care centre in Himachal Pradesh between July 2015 and June 2016. All the indoor patients with age above 18 years with a diagnosis of scrub typhus were included in this study. Results: Out of total 180 patients, 130 were female patients. Most patients were in the age group 21-30 (23.3%). All the patients presented with history of fever, but 54 patients presented with high grade fever. Other Most common symptom was chills and rigours (81%), followed by vomiting and headache each 32%, cough 31%. On examination 21% patients had eschar,14% patients had lymphadenopathy. Most number of patients presented in the month of September (51.6%), followed by August (33.3%). Conclusion: Scrub typhus being an important differential of acute undifferentiated fever in this region, should not be missed by primary care physicians, as once multi organ dysfunction sets in, mortality rate starts rising. So, there is a high need of sensitization of doctors and people about this illness so that early diagnosis and early treatment can be ensured.